Factors Influencing the Location Decision in Southern China for Western Business - Yuan, T (2009)
This paper tends to investigate the true situation in China regarding to location decisions. It mainly provides an answer to what factors should be aware in selecting location by western business moving to China. Moreover, the ‘why question’ is answered in the form of discovering the drivers of those literature-to-realistic differences and how the real situation matching the theories. The results of the research are made according to the China’s actual situation and general literatures provided by other authors, and the interpretations are supported by particular business insights collected from several interviews.